Early childhood caries and infant’s oral health; pediatricians’ and family physicians’ practice, knowledge and attitude in Riyadh city, Saudi Arabia - Renad Alshunaiber; Haya Alzaid; Shahad Meaigel; Arwa Aldeeri; Abdallah Adlan (Saudi Dental Journal)
Background: Early childhood caries (ECC) is a significant worldwide oral health problem. However, parents do not take their children to the dentist for regular screening of oral diseases as early as they do with pediatricians and family physicians. As a result, pediatricians and family physicians are considered as a reliable and perfect source for children’s oral health promotion and disease prevention. Studies assessing pediatricians’ and family physicians’ practice, knowledge and attitude regarding ECC and infant’s oral health in Saudi Arabia are few. As a result, this study aimed to assess these aspects. Methodology: A cross-sectional study based on a structured close-ended questionnaire was conveniently distributed among pediatricians and family physicians in Riyadh city, Saudi Arabia. The questionnaire composed of two main sections; demographic characteristics and questions assessing participants’ practice, knowledge and attitude. The data was analyzed using SAS software, frequency and chi-square test were conducted, and P-value of <0.05 and less was considered significant. Results: There was a discrepancy between the participants’ knowledge, attitude and practice. The participants’ practice was lower (42.6%) compared with their attitude (86.1%) and knowledge (65.3%). Most of the participants (52.5%) indicated lack of clinical time was the main barrier for performing oral health related activities. Majority of the participants (76.7%) indicated that they need more dental training and education. Dental caries preventive methods (44.6%) was the most requested topic, of which workshops and seminars were the main preferred method (39.6%). Conclusion: Although most of the participants reported good dental attitude and knowledge, a lack of the associated dental practice was detected. Therefore, more efforts are encouraged to enhance and facilitate dental practice among pediatricians and family physicians. Keywords: Oral health, Attitude, Knowledge, Practice, Pediatricians, Family physicians